Adipose tissue radiodensity and mortality among patients with nonmetastatic breast cancer. Issue 12 (December 2022) - Cheng, En; Caan, Bette J.; Chen, Wendy Y.; Irwin, Melinda L.; Prado, Carla M.; Cespedes Feliciano, Elizabeth M.
Summary: Background & aims: Computed tomography (CT) scans can measure quantity and distribution of adipose tissue, which are associated with breast cancer prognosis. As a novel prognostic marker, radiodensity of adipose tissue has been examined in multiple cancer types, but never in breast cancer. Lower density indicates larger adipocytes with greater lipid content, whereas higher density can reflect inflammation, fibrosis, vascularity, or even metabolic changes; and both may impact breast cancer prognosis. Methods: We included 2868 nonmetastatic patients with breast cancer diagnosed between January 2005 and December 2013 at Kaiser Permanente Northern California, an integrated healthcare system. From CT scans at diagnosis, we assessed the radiodensity of subcutaneous (SAT) and visceral adipose tissue (VAT) at the third lumbar vertebra and categorized their radiodensity into three levels: low (<1 standard deviation [SD] below the mean), middle (mean ± 1 SD), and high (>1 SD above the mean). Using multivariable Cox proportional hazards regression with adjustment for clinicopathological characteristics including body mass index, we calculated hazard ratios (HRs [95% confidence intervals]) for the associations of adipose tissue radiodensity with overall mortality and breast-cancer-specific mortality. Results: Median age at diagnosis of breast cancer was 56.0 years, most (63.3%) were non-Hispanic White and nearly half (45.6%) were stage II. Compared to middle SAT radiodensity, high SAT radiodensity was significantly associated with increased risk of overall mortality (HR: 1.45 [1.15–1.81]), non-significantly with breast-cancer-specific mortality (HR: 1.32 [0.95–1.84]). Neither low SAT radiodensity nor high or low VAT radiodensity was significantly associated with overall or breast-cancer-specific mortality. Conclusions: High radiodensity of SAT at diagnosis of nonmetastatic breast cancer was associated with increased risk of overall mortality, independent of adiposity and other prognostic factors. Considering both radiodensity and quantity of adipose tissue at different locations could deepen understanding of the role of adiposity in breast cancer survival.